Analisis Manajemen Mutu di Madrasah Ibtidaiyah Muhammadiyah Program Tahfidz Majenang Kabupaten Cilacap - Hanipudin, Sarno; Dwi Endriyanto, Adam (Adaara: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to describe and analyze the implementation of Total Quality Management (TQM) in improving school services at MI Muhammadiyah Majenang. The study utilizes a qualitative approach with a case study method. Data is collected through observations, interviews, and reviewing documents and records related to the research. The findings of this research indicate that the implementation of TQM at MI Muhammadiyah Majenang has improved customer satisfaction, as evidenced by the increasing enrollment at MI Muhammadiyah Majenang. Continuous improvements are made by the school, leading to numerous achievements by teachers and students. However, it is also found that one inhibiting factor in the implementation of TQM at MI Muhammadiyah Majenang is the lack of commitment from some parties in the long term. This finding suggests the need for synergy in implementing TQM, where the school head, as a leader, should provide motivation and involve all levels of management, teachers, and staff to take responsibility and instill confidence in determining the quality to be achieved, thus upholding their commitment to improving school services.